2016
DOI: 10.1167/iovs.15-18843
|View full text |Cite
|
Sign up to set email alerts
|

OCT-Based Macular Structure–Function Correlation in Dependence on Birth Weight and Gestational Age—the Giessen Long-Term ROP Study

Abstract: Increased thicknesses of the entire retina or specific layers at the fovea did not correlate with functional loss; but a thinner ONL in retinae without foveal pit did. This reduced ONL+ ratio is potentially caused by a reduced foveal cone density and may be the first morphologic functional correlate in prematurity and ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
69
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 30 publications
16
69
1
6
Order By: Relevance
“…Previous studies observed a decrease in VEGF expression in the choroid in 1-month-old rats subjected to oxygen-induced retinopathy [26]. While ROP has been shown to cause central and peripheral visual disorder, the exact cause of these deficits is not known [6, 27, 28]. In an animal ROP model, Shao et al [3] found that an involution of choroid tissue and choriocapillaris, which supplies nutrients and oxygen to the outer retina, was an important contributor to reduced cone and rod function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies observed a decrease in VEGF expression in the choroid in 1-month-old rats subjected to oxygen-induced retinopathy [26]. While ROP has been shown to cause central and peripheral visual disorder, the exact cause of these deficits is not known [6, 27, 28]. In an animal ROP model, Shao et al [3] found that an involution of choroid tissue and choriocapillaris, which supplies nutrients and oxygen to the outer retina, was an important contributor to reduced cone and rod function.…”
Section: Discussionmentioning
confidence: 99%
“…We measured the following: retinal nerve fiber layer (NFL), ganglion cell layer plus inner plexiform layer (GCL + IPL), INL plus outer plexiform layer (INL + OPL), ONL plus external limiting membrane (ONL + ELM), inner segment plus inner ellipsoid segment of the photoreceptor layer plus outer segment of the photoreceptor layer (ISe + OS), and retinal pigment epithelium (RPE). The ratio of ONL + ELM to the sum of inner retinal layers (NFL + GCL + IPL + INL + OPL = IRL) overlying the foveal center was calculated, as described in our previous publication [6]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations